Scientific Literacy Achievements in PISA and Their Implications for Science Education Reform in Developing Countries - Yuyu Wahyudin; Rexford Baah; Chin Peng Ching (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze science literacy achievement based on PISA results and compare the performance of ASEAN and African countries. It also seeks to examine the implications of PISA science literacy outcomes for the development and improvement of science education in developing countries. Methodology: This study employed a descriptive qualitative and quantitative document analysis. Secondary data were obtained from official OECD PISA 2018 and 2022 reports. Content analysis and descriptive-comparative analysis were applied. Data processing and tabulation were conducted using Microsoft Excel, supported by a systematic literature review of peer-reviewed science education journals. Main Findings: The results show that science literacy achievement in ASEAN and African countries remains below the OECD average. ASEAN countries demonstrate relatively higher scores than African countries, although most students are still at basic literacy levels. Significant gaps exist between developing countries and high-performing PISA participants in scientific reasoning and problem-solving skills. Novelty/Originality of this study: The study offers a comparative cross-regional analysis of PISA science literacy between ASEAN and African countries, which is rarely addressed in previous research. It integrates PISA data with science literacy theory to provide policy-relevant insights for science education development in developing countries, contributing to a broader Global South perspective in PISA-based studies.